On the accuracy of economic observations - Morgenstern, Oskar (Princeton, N.J., Princeton University Press, 1963)
Economic observation through data, mass observation and the analysis of time.
Bibliography: p. 307-315.
sju 22/01/2019
Loans
Keywords: Economics, Mathematical; Economic observations